2014
DOI: 10.5578/kvj.7963
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure In Buffalo Calves

Abstract: Kocatepe Vet J 2014 7(2): 1-8 1 S U M M A R YThis study was carried out for the determination and the evaluation of intraocular pressure (IOP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Although the IOP values obtained from calves’ right and left eyes differed, these values were found to be statistically insignificant. Çetin et al ( 2014 ) also found insignificantly different IOP values for the right and left eyes of young buffalo calves using a Tonopen-XL Applanation Tonometer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the IOP values obtained from calves’ right and left eyes differed, these values were found to be statistically insignificant. Çetin et al ( 2014 ) also found insignificantly different IOP values for the right and left eyes of young buffalo calves using a Tonopen-XL Applanation Tonometer.…”
Section: Discussionmentioning
confidence: 96%
“…Sedation and topical anaesthesia as two of the many factors such as measurement time (hour), breed, exercise, postural changes, medicines, blood pressure and seasonal changes (Çetin, Pamuk & Yaprakçı 2014 ; Gum et al 1998 ) were eliminated by using the Icare ® Rebound Tonometer. Çetin et al ( 2014 ) conducted a study on young buffalo calves and assessed the results by making IOP measurements at the same time (hours) of day. It was reported that in this way they get safer results.…”
Section: Discussionmentioning
confidence: 99%